Tinjauan Yuridis Tentang Alasan Perceraian: (Studi Putusan Nomor 1258/Pdt.G/2020/PA.Pra) - Rindang Suci Amalia; Fatahullah Fatahullah; Eka Jaya Subadi (Fakultas Hukum Universitas Mataram, 2023)
This research purposes are to know judge’s consideration of decision for case number 1258/Pdt.G/2020/PA.Pra whether has been in line with the applicable regulations and also to know the legal consequences of divorce towards “hadhanah” children rights. This research applied normative legal method. Results of the study show that judge granted the divorce request according to the Art 19 Law Number 1 of 1974 on Marriage jo. Art 19 Number 9 Government Regulation Number 1975 jo Art 11 letter (f) Islamic Compilation Law. Legal consequence of the divorce towards children rights are fall under the parents especially the father until the child is mature.